2017
DOI: 10.1051/epjconf/201714003004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of gravity-driven granular discharge flow under the influence of an obstacle

Abstract: Abstract. Two-dimensional granular discharge flow driven by gravity under the influence of an obstacle is experimentally investigated. A horizontal exit of width W is opened at the bottom of vertical Hele-Shaw cell filled with stainless-steel particles to start the discharge flow. In this experiment, a circular obstacle is placed in front of the exit. Thus, the distance between the exit and obstacle L is also an important parameter. During the discharge, granular-flow state is acquired by a high-speed camera. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
4
3
0
Order By: Relevance
“…This tendency is consistent with the flow rate reduction due to the obstacle effect [25,30]. Note that, the discharge flow rate is always steady independently of obstacle shapes [25,30]. In Fig.…”
Section: Vertical Velocitysupporting
confidence: 81%
See 2 more Smart Citations
“…This tendency is consistent with the flow rate reduction due to the obstacle effect [25,30]. Note that, the discharge flow rate is always steady independently of obstacle shapes [25,30]. In Fig.…”
Section: Vertical Velocitysupporting
confidence: 81%
“…3(a)), the relation between the clogging and the circular obstacle is not so clear. Moreover, we have confirmed that discharge flow rate is almost always steady even in the alternate flow regime [30].…”
Section: B Granular Flow Fieldsupporting
confidence: 71%
See 1 more Smart Citation
“…1. The system is basically identical to that used in 3,24 . We built a two-dimensional (2D) granular silo with a horizontal bottom wall.…”
Section: Introductionmentioning
confidence: 99%
“…However, the typical flow features for granular silo flow (e.g., steadiness independent of layer's thickness) are preserved in this system. More detail characterization and the study on clogging with this experimental system are reported in 3,24 . The videos of particle motions can be found in 26 .…”
Section: Introductionmentioning
confidence: 99%